2017
DOI: 10.1007/s12011-017-1144-6
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Serum Copper Status and Neonatal Birth Outcomes: a Prospective Cohort Study

Abstract: Our study aimed to assess the distribution of copper (Cu) in umbilical cord serum and estimated the association between umbilical serum Cu status and neonatal birth outcomes in a Chinese population. Through the Ma'anShan Birth Cohort Study, 2689 maternal-singleton pairs with detailed birth records and available serum samples were identified. The tertile levels of ln-transformed Cu were used to define low, medium, and high levels for serum Cu. The median for umbilical cord serum Cu was 298.2 μg/L with a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
4
24
2
Order By: Relevance
“…Very little information was found in the literature on the maternal serum concentrations of the trace elements selenium, copper, and zinc in pregnancy and their associations with spontaneous preterm birth in the African region. Comparing with researches from other regions, some studies have found maternal concentrations of these trace elements to be associated with preterm birth, while others have reported no associations [20,24,[35][36][37][38][39]. In this study, higher selenium concentrations were observed in the maternal serum of preterm birth, but this was not significant.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…Very little information was found in the literature on the maternal serum concentrations of the trace elements selenium, copper, and zinc in pregnancy and their associations with spontaneous preterm birth in the African region. Comparing with researches from other regions, some studies have found maternal concentrations of these trace elements to be associated with preterm birth, while others have reported no associations [20,24,[35][36][37][38][39]. In this study, higher selenium concentrations were observed in the maternal serum of preterm birth, but this was not significant.…”
Section: Resultscontrasting
confidence: 91%
“…Copper is an essential cofactor for numerous enzymes involved in various biological processes. The effect of maternal copper concentration is not well understood with some studies suggesting increased preterm birth with copper deficiency [20][21][22][23] and others reporting no association [24,25]. Zinc is a crucial component of many metalloenzymes participating in protein and carbohydrate metabolism, nucleic acid synthesis, and antioxidant functions through the Cu/Zn superoxide dismutase [26].…”
Section: Introductionmentioning
confidence: 99%
“…Very little information was found in the literature on the maternal serum concentrations of the trace elements selenium, copper and zinc in pregnancy and their associations with spontaneous preterm birth in the African region. Comparing with researches from other regions some studies have found maternal concentrations of these trace elements to be associated with preterm birth, while others have reported no associations [21], [25], [36]- [40]. In this study, higher selenium concentrations were observed in maternal serum of preterm birth, but this was not significant.…”
Section: Two-way Associations With Being Preterm Birthcontrasting
confidence: 89%
“…Spontaneous preterm birth reduces the pregnancy duration with resultant increased maternal serum concentrations and reduced fetal hepatic stores. Clinical research indicate that serum concentrations of selenium, copper, and zinc are higher in term infants than preterm infants [21]- [24], [44]- [46]. Consequently, with adequate nutrition, serum concentrations of selenium, copper and zinc would be expected to be higher in serum of women delivering preterm as there is reduced time for the mother to pass these trace elements to placenta and fetus.…”
Section: Two-way Associations With Being Preterm Birthmentioning
confidence: 99%
See 1 more Smart Citation